Argentine Public Universities: Inefficient and Ineffective? - Rabossi, Marcelo (International Higher Education, 2013)
Although Argentina prides itself on having the highest gross university enrollment rate in Latin America, the relative low proportion of graduates has put the open and free-for-all national university under pressure and questioning. In a national system where in more than one third of all public drop-out rates are above 80 percent, an urgent reform is needed.